Bismuth-Integrated Nitrogen-Doped Carbon Nanostructures Enabling Broad Electrolyte Compatibility for Mg-Ion Batteries - No, Woo Joo; Han, Jonghyun; Kim, Mingony; Choi, Jihwan; Chung, Kyung Yoon; Lee, Kwan-young; Oh, Si Hyoung (WILEY-V C H VERLAG GMBH, 2026)
Bismuth has emerged as a promising alloying anode for magnesium-ion batteries (MIBs), offering high theoretical capacity with a low electrode potential, and thus serving as a viable alternative to Mg metal. Herein, Bi nanoparticle (NP)-integrated nitrogen-doped carbon nanostructures (Bi@nCN) are synthesized via a scalable one-step carbothermal reduction of BiOCl and Mg phthalocyanine. The resulting Bi@nCN features finely dispersed Bi NPs embedded in a nitrogen-doped carbon matrix, forming a stress-relieving architecture that accommodates the structural changes associated with the two-phase reaction between Bi and Mg3Bi2. Bi@nCN demonstrates excellent electrochemical performance, with high capacity retention, superior rate capability, and minimal polarization growth. Furthermore, full cells employing Bi@nCN anodes exhibit stable operation in chloride-free electrolytes, including ether- and nitrile-based systems, in which Mg metal typically develops insulating passivation layers. These findings highlight the potential of Bi@nCN to enable stable Mg-ion storage in chloride-free electrolytes, overcoming the intrinsic limitations of Mg metal anodes and expanding the scope of MIB chemistry with new electrolyte and cathode combinations.